Acceptance of COVID-19 vaccine among sub-Saharan Africans (SSA): a comparative study of residents and diasporan dwellers - Chundung Asabe Miner; Chikasirimobi G. Timothy; Khathutshelo Percy; Mashige; Uchechukwu Levi Osuagwu; Esther Awazzi Envuladu; Onyekachukwu Mary-Anne Amiebenomo; Godwin Ovenseri-Ogbomo; Deborah Donald Charwe; Piwuna Christopher Goson; Bernadine N. Ekpenyong; Emmanuel Kwasi Abu; et al. (BMC Public Health, 2023)
Abstract Background The COVID-19 vaccines are being rolled out across all the sub-Saharan Africa (SSA) countries, with countries setting targets for achieving full vaccination rates. The aim of this study was to compare the uptake of, resistance and hesitancy to the COVID-19 vaccine between SSA locally residents and in the diasporan dwellers. Methods This was a cross-sectional study conducted using a web and paper-based questionnaire to obtain relevant information on COVID-19 vaccine acceptance. The survey items included questions on demography, uptake and planned acceptance or non-acceptance of the COVID-19 vaccines among SSAs. Multinomial logistic regression was used to determine probabilities of outcomes for factors associated with COVID-19 vaccination resistance and hesitancy among SSA respondents residing within and outside Africa. Results Uptake of COVID-19 vaccines varied among the local (14.2%) and diasporan (25.3%) dwellers. There were more locals (68.1%) who were resistant to COVID-19 vaccine. Participants’ sex [adjusted relative risk (ARR) = 0.73, 95% CI: 0.58 – 0.93], education [primary/less: ARR = 0.22, CI:0.12 – 0.40, and bachelor’s degree: ARR = 0.58, CI: 0.43 – 0.77]), occupation [ARR = 0.32, CI: 0.25—0.40] and working status [ARR = 1.40, CI: 1.06—1.84] were associated with COVID-19 vaccine resistance among locals. Similar proportion of local and diasporan dwellers (~ 18% each) were hesitant to COVID-19 vaccine, and this was higher among health care workers [ARR = 0.25, CI: 0.10 – 0.62 and ARR = 0.24, CI:0.18—0.32, diaspora and locals respectively]. After adjusting for the potential confounders, local residents aged 29–38 years [ARR = 1.89, CI: 1.26—2.84] and lived in East Africa [ARR = 4.64, CI: 1.84—11.70] were more likely to report vaccine hesitancy. Knowledge of COVID vaccines was associated with hesitancy among local and diasporan dwellers, but perception was associated with vaccine resistance [ARR = 0.86,CI: 0.82 – 0.90] and hesitancy [ARR = 0.85, CI: 0.80 – 0.90], only among the local residents. Conclusions Differences exist in the factors that influence COVID-19 vaccine acceptance between local SSA residents and thediasporan dwellers. Knowledge about COVID-19 vaccines affects the uptake, resistance, and hesitancy to the COVID-19 vaccine. Information campaigns focusing on the efficacy and safety of vaccines could lead to improved acceptance of COVID-19 vaccines.